Processes controlling the distribution of dissolved Al and Ga along the U.S. GEOTRACES East Pacific Zonal Transect (GP16). (May 2019) - Ho, Peng; Resing, Joseph A.; Shiller, Alan M.
Abstract: Gallium (Ga) behaves similarly to aluminum (Al) in the ocean. However, there are key differences in their behaviors resulting from the small differences in their chemistry. Here we present the distributions of dissolved Ga and Al in the Eastern Tropical Pacific Ocean, obtained as part of the 2013 U.S. GEOTRACES GP16 Eastern Pacific Zonal Transect (EPZT) from Peru to Tahiti. Low surface water dissolved Ga and Al, as well as high and variable surface water Ga/Al ratios along the EPZT reflect low aeolian input and a longer Ga residence time than Al. A gradient of decreasing surface water Ga toward the Peru upwelling region but not seen in surface water Al can be explained by additional dissolved Al inputs from shelf sediments, the presence of less reactive Al species or advection of low-Ga water from elsewhere. Beyond the coastal upwelling zone, the absence of Ga and Al removal associated with the chlorophyll a maximum suggests minimal removal of Al and Ga by biological scavenging in the oligotrophic gyre waters in the EPZT. West of 105°W, an expanding shallow pool (<200 m) of Ga-enriched water suggests Ga accumulation within the gyre circulation. However, we did not observe dissolved Al enrichment in this Ga-enriched pool. West of 90°W, a dissolved Ga minimum is centered within the nutricline, right below the Ga-enriched pool, and is likely a result of advective input of low-Ga water. Anomalously high dissolved Al water in the upper 200 m at the middle of section (106–112°W) was not an artifact of contamination, though the reasons for this remain unknown. Slightly elevated dissolved Al was observed near the Peru margin and at mid-depth in the western part of the section. Surprisingly, this mid-depth dissolved Al enrichment in the west is more prominent than that on the Peru margin. This may result from greater biological Al removal along the margin and/or different dust sources with differing Al solubility. A Ga depletion was commonly observed in the intermediate waters, especially near the Peru margin. This is opposite from the observation of slightly increased Al in these waters and still remains to be explained. Generally, elevated deep water Ga and Al concentrations were observed in this section, indicating inputs from hydrothermal activity and resuspended sediments. However, ∼930 km east of the East Pacific Rise, decreased bottom water Al, even in the nepheloid layer, might be due to low Al dissolution from these resuspended hydrothermal particles and/or the advection of low-Al Pacific Deep Water from the north. West of 143°W, decreased Ga and increased dissolved Al near the bottom indicate Antarctic Bottom Water influence. In the hydrothermal plumes, dissolved Ga and Al behavior is largely regulated by dilution of the hydrothermal signal. Hydrothermal Al flux estimates show hydrothermal inputs of Al are likely to be of regional, not global importance while the hydrothermal Ga flux might be comparable to the aeolian Ga flux. Highlights: Low surface water Ga and Al in the eastern Pacific Ocean due to low dust input. Increased Al at mid-depth in western part of transect and on the Peru margin. Ga depletion commonly observed in the intermediate waters. Elevated deep water Ga and Al associated with resuspended sediments. Hydrothermal inputs of Al likely to be of regional, not global importance.